Copy-number changes in evolution: rates, fitness effects and adaptive significance - Katju, Vaishali; Bergthorsson, Ulfar (Frontiers in Genetics, 2013)
Gene copy-number differences due to gene duplications and deletions are rampant in natural populations and play a crucial role in the evolution of genome complexity. Per-locus analyses of gene duplication rates in the pre-genomic era revealed that gene duplication rates are much higher than the per nucleotide substitution rate. Analyses of gene duplication and deletion rates in mutation accumulation lines of model organisms have revealed that these high rates of copy-number mutations occur at a genome-wide scale. Furthermore, comparisons of the spontaneous duplication and deletion rates to copy-number polymorphism data and bioinformatic-based estimates of duplication rates from sequenced genomes suggest that the vast majority of gene duplications are detrimental and removed by natural selection. The rate at which new gene copies appear in populations greatly influences their evolutionary dynamics and standing gene copy-number variation in populations. The opportunity for mutations that result in the maintenance of duplicate copies, either through neofunctionalization or subfunctionalization, also depends on the equilibrium frequency of additional gene copies in the population, and hence on the spontaneous gene duplication (and loss) rate. The duplication rate may therefore have profound effects on the role of adaptation in the evolution of duplicated genes as well as important consequences for the evolutionary potential of organisms. We further discuss the broad ramifications of this standing gene copy-number variation on fitness and adaptive potential from a population-genetic and genome-wide perspective.